Role of killer factors in the inhibitory activity of bio-control yeasts against Penicillium expansum and Aspergillus ochraceus - Portes,Ciro da Silva (2013)
This work evaluated the antagonism of killer positive yeast strains (isolated from 11 samples of different frozen fruit pulps) against the strains of Penicillium expansum and Aspergillus ochraceus. Of the total 41 killer yeasts tested in YM agar, 19 showed antibiosis against P. expansum and A. ochraceus, with inhibition zone ranging from 10 to 18 mm and 10 to 19 mm, respectively. In the following step, the extracellular activity of Kluyveromyces sp. FP4(13) was tested performing the assay in YM broth. The antifungal activity of Kluyveromyces sp. FP4(13) cell-free culture supernatant (25ºC/96 h) was more effective against the conidia germination, showing inhibition rates of 93.33 and 86.44% for P. expansum and A. ochraceus, respectively. The micelial growth inhibition was 28.45 and 21.0%, respectively. The antagonism showed by the selected yeasts could be used as a promising alternative tool to reduce and control the postharvest fungal spoilage of the fruits. However, further studies should be carried out in order to better elucidate the role of innocuous characters in antagonistic microorganisms, as well as the purification and characterization of new killer toxins.